Hábitos de vida, sarcopenia e estado nutricional de idosos frequentadores de um centro de convivência de Belém-PA - LEITE, Thaissa Carolina Pacheco (2023)
Introduction: Aging adds changes in the body composition of individuals and one of the most striking is the progressive loss of muscle mass, strength and function, known as sarcopenia, possibly associated with imbalances in their nutritional state. Objective: To verify the life habits, nutritional status and occurrence of sarcopenia in elderly people of a community group in the city of Belem-PA. Method: Descriptive, crosssectional study with a quantitative approach carried out with 22 elderly people assisted by a pastoral action in the neighborhood of Guamá. In the study were used the evaluation of muscle mass (MM) and physical performance for the diagnosis of sarcopenia: one MM was evaluated by calf circumference (CC); the palmar grip strength (PGS) was quantified with the aid of a digital dynamometer; the usual gait velocity test (VT) was performed in a space measured at 10 m; using three different combinations of methods. In the evaluation of nutritional status, the Body Mass Index (BMI). Results: Regarding the nutritional diagnosis, the sample expressed in BMI 11% in malnutrition, 57% in eutrophy and 32% in excess weight; malnourished patients had severe sarcopenia; the obese, degrees of sarcopenia. Conclusion: Both malnourished and obese elderly patients presented with sarcopenia, which is why orientation to regular physical activity preserves active muscle mass and slows the onset or muscle depletion. Adequate food and nutrition education, access to quality food, and public policies aimed at health promotion should stimulate the elderly to develop physical activity, maintain adequate weight and have quality of life.